Associations between serum hepcidin, ferritin and Hb concentrations and type 2 diabetes risks in a Han Chinese population. Issue 12 (7th June 2013) - Guo, Xin; Zhou, Daizhan; An, Peng; Wu, Qian; Wang, Hao; Wu, Aimin; Mu, Mingdao; Zhang, Di; Zhang, Zhou; Wang, Hui; He, Lin; Liu, Yun; et al.
Abstract : Systemic Fe overload can contribute to abnormal glucose metabolism and the onset of type 2 diabetes (T2D). Although hepcidin is the master regulator of systemic Fe homeostasis, few studies have systematically evaluated the associations of serum hepcidin concentrations with Fe metabolism parameters and risks for the development of T2D. In this regard, whether hepcidin concentrations are associated with T2D remains controversial. We measured serum hepcidin and ferritin concentrations in a case–control study of 1259 Han Chinese participants to evaluate the possible associations of serum hepcidin concentrations with Fe metabolism parameters and risks of T2D. Individuals with diabetes ( n 555) and control participants ( n 704) were recruited and serum hepcidin and ferritin concentrations were quantified. Additionally, selected biochemical and anthropometric variables were determined. A logistic regression analysis was performed to evaluate the association of serum hepcidin and ferritin concentrations with T2D. A linear regression analysis was used to test for associations between serum hepcidin and ferritin concentrations and a number of clinical, demographic and diabetes-associated variables. We found that serum hepcidin concentrations correlated with Hb and serum ferritin concentrations. No differences in hepcidin concentrations were found between the group with diabetes and the control group. Hepcidin concentrations were not significantly correlated with T2D risk factors. We also found that serum ferritin concentrations were elevated in individuals with diabetes and were positively correlated with both Hb concentrations and T2D risk factors. The present findings suggest that serum ferritin concentrations correlate with T2D risk factors, while serum hepcidin concentrations are positively associated with Hb and serum ferritin concentrations, but do not correlate with T2D.